2018
DOI: 10.1103/physrevb.98.075410
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of the adsorption height of graphenelike adsorbates on their dimensionality

Abstract: Comparing the adsorption heights of various graphene nanoribbons on Cu(111) and Au(111) surfaces to those of graphene and π-conjugated planar organic molecules, we observe that two-dimensional graphene adsorbs much further away from the surface than both one-dimensional graphene nanoribbons and π-conjugated planar molecules-which represent zero-dimensional graphene flakes. We show that this is a direct consequence of the adsorbates' dimensionality. Our results provide invaluable insights into the interplay of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…The results suggested the possibility of a 3D intramolecular distortion, which was not directly accessible via STM. Such a distortion was previously determined using the X-ray standing-wave technique for equally small hydrocarbons, such as perylenetetracarboxylic dianhydride (PTCDA) 24 and pentacene, 25 adsorbed on noble metal surfaces.…”
Section: ■ Resultsmentioning
confidence: 99%
“…The results suggested the possibility of a 3D intramolecular distortion, which was not directly accessible via STM. Such a distortion was previously determined using the X-ray standing-wave technique for equally small hydrocarbons, such as perylenetetracarboxylic dianhydride (PTCDA) 24 and pentacene, 25 adsorbed on noble metal surfaces.…”
Section: ■ Resultsmentioning
confidence: 99%
“…2c). This is caused by the strong concave distortion of the dehydrogenated bisanthene derivatives, resulting from chemical bonds that form between unsaturated edge carbons and the Cu(110) surface 33 .…”
Section: Resultsmentioning
confidence: 99%
“…The polymerisation of 10,10′-dibromo-9,9′-bianthracene (DBBA, C 28 H 16 Br 2 ) on metal surfaces is used for the on-surface synthesis of graphene nanoribbons 2731 and graphene 30,32,33 . The reaction is thermally activated and proceeds via dehalogenation and cyclodehydrogenation.…”
Section: Introductionmentioning
confidence: 99%
“…Using angle-resolved photoelectron spectroscopy (ARPES) it was shown that QFMLG formed in this way is n-type doped. However, no information about the vertical structure of this system has been reported, such as the thickness of the Sb layer and its vertical distances to the graphene layer and to the substrate, although such information is highly relevant: The layer distance is an excellent indicator of interaction strength [19,[29][30][31][32][33]. The thickness of the intercalated layer can affect the electronic properties and the possible application of the system, as in the case of two dimensional Ag layers on epitaxial graphene [23].…”
Section: Introductionmentioning
confidence: 99%